Forming research competencies of higher school students with multi-level tasks - I. M. Agibova; M. A. Bedzhanyan; O. A. Nechaeva; O. V. Fedina (Вестник Северо-Кавказского федерального университета)
Introduction. At present, when dynamic transformations are taking place in all spheres of society, and the technological progress is simply ahead of time, production is being modernized, science is developing, the state needs specialists with high creative potential. To train such specialists, it is necessary to change the priorities in education, focusing on the independent cognitive activity of students. Research activity is becoming an essential part of learning, and the formation of students’ research competencies is the goal of their teachers. Goal. Therefore, the purpose of our work was to find an answer to the question of how to increase the level of formation of research competencies of higher school students.Materials and methods. The article presents creative tasks developed by the authors and methods of their application in a laboratory workshop for undergraduate students in the field of Physics. The tasks are close to scientific research, they involve the use of complex experimental facilities and the study of materials whose properties have not yet been fully studied. The tasks are divided into three levels: complex, medium and simple, which allows the authors to propose a new methodology for organizing their implementation, taking into account the different abilities of students. The teacher acts as an assistant in the search for ideas for solving the next task.Results and discussion. A pedagogical experiment using the methodology of the authors of the article for the formation of research competencies was conducted on the basis of the NCFU Department of Experimental Physics. To conduct the experiment, the students were divided into two groups – the control one and the experimental one. The control group performed standard laboratory work according to ready-made instructions, using standard techniques. The experimental group additionally performed tasks close to scientific research.Conclusion. The experiment was conducted over the course of a year and showed that additional creative tasks performed by students using the proposed methodology cannot only increase the level of formation of research competencies but also enhance students’ motivation for scientific activity.